2015
DOI: 10.1109/jphot.2015.2438432
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Fiber-Optic Parametric Amplifier Based on Near-Zero Ultraflat Dispersion PCF for Communication Wavelength

Abstract: In this article, a new technique to attain a tunable parametric amplifier for application in the communication wavelength, based on near zero ultra-flat dispersion with PCF, has been explored. The chromatic dispersion profile and the corresponding ZDW of the optimized PCF can be well tuned to provide a wide gain spectrum in the communication wavelength just by changing the temperature of the fiber. A detail investigation reveals that the fiber retains its near-zero ultra flat nature when the temperature is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The capabilities of an already fabricated PCF are further enhanced by filling the air holes of the cladding with suitable materials: liquid [16], gas [17], or polymer [18]. Successful demonstration of tunable FWM in holey/thermooptic liquid-filled PCF and liquid crystal filled PCF has been done by changing the temperature and electric field, respectively [19][20][21][22][23]. Such a tailorable nonlinear process allows the imaging of different molecular elements using a single source [24].…”
Section: Introductionmentioning
confidence: 99%
“…The capabilities of an already fabricated PCF are further enhanced by filling the air holes of the cladding with suitable materials: liquid [16], gas [17], or polymer [18]. Successful demonstration of tunable FWM in holey/thermooptic liquid-filled PCF and liquid crystal filled PCF has been done by changing the temperature and electric field, respectively [19][20][21][22][23]. Such a tailorable nonlinear process allows the imaging of different molecular elements using a single source [24].…”
Section: Introductionmentioning
confidence: 99%
“…Maji and Chaudhuri [7] investigated fiber parameters such as fiber length, pump power and pump wavelength towards the analytical FOPA gains of three ZDW in the near-zero ultra-flat photonic crystal fibers (PCF) around the communication wavelength by tuning pumping condition. A study in [8] concluded that by changing temperature of the fiber and tuning the chromatic dispersion profile and ZDW of the optimized PCF, then a wide gain spectrum in the communication wavelength can be achieved .…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to optimize the FOPA gain spectrum for instance by increasing the pump power to obtain high parametric gain [7] and place the pump close to zero dispersion frequency to attain wide amplification bandwidth [8]. Either way, one can also include the higher-order dispersion coefficient of a fiber in order to optimize the FOPA gain spectrum.…”
Section: Introductionmentioning
confidence: 99%